Dialysis complications in AKI patients treated with extended daily dialysis: is the duration of therapy important? - Albino, Bianca Ballarin [UNESP]; Balbi, Andre Luis [UNESP]; Ponce, Daniela [UNESP] (Hindawi Publishing Corporation, 2014)
This trial aimed to compare the dialysis complications occurring during different durations of extended daily dialysis (EDD) sessions in critically ill AKI patients. We included patients older than 18 years with AKI associated with sepsis admitted to the intensive care unit and using noradrenaline dose ranging from 0.3 to 0.7 mu g/kg/min. Patients were divided into two groups randomly: in G1, 6 h sessions were performed and, in G2, 10 h sessions were performed. Seventy-five patients were treated with 195 EDD sessions for 18 consecutive months. The prevalence of hypotension, filter clotting, hypokalaemia, and hypophosphataemia was 82.6, 25.3, 20, and 10.6%, respectively. G1 and G2 were similar in male predominance and SOFA. There was no significant difference between the two groups in hypotension, filter clotting, hypokalaemia, and hypophosphataemia. However, the group treated with sessions of 10 hours showed higher refractory to clinical measures for hypotension and dialysis sessions were interrupted more often. Metabolic control and fluid balance were similar between G1 and G2. In conclusion, intradialysis hypotension was common in AKI patients treated with EDD. There was no difference in the prevalence of dialysis complications in patients undergoing different durations of EDD.